2020
DOI: 10.1007/s00234-020-02500-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance parkinsonism indices and interpeduncular angle in idiopathic normal pressure hydrocephalus and progressive supranuclear palsy

Abstract: Purpose The clinical presentation of idiopathic normal pressure hydrocephalus (iNPH) may overlap with progressive supranuclear palsy (PSP). The Magnetic Resonance Parkinsonism Index (MRPI), MRPI 2.0, and the interpeduncular angle (IPA) have been investigated to differentiate PSP from healthy controls (HC) and other parkinsonisms. We aimed to assess equivalences and differences in MRPI, MRPI 2.0, and IPA in iNPH, PSP, and HC groups. Methods We retrospectively recruited 99 subjects (30 iNPH, 32 PSP, 37 HC) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Traditionally, NPH and PSP are classified as two distinct diseases and should be thoroughly distinguished to avoid futile treatment. Several researchers tried to find additional MRI indexes differentiating one from the other, such as Magnetic Resonance Parkinsonism Index, Magnetic Resonance Hydrocephalic Index, interpeduncular angle, midbrain area, and cortical thickness (Bianco et al., 2022; Ohara et al., 2020 ; Quattrone et al., 2020 ; Ugga et al., 2020 ; Virhammar et al., 2022). In our opinion, a portion of the two entities does overlap and share similar features, implying the transitory role of NPH mimics in the clinical course of PSP.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, NPH and PSP are classified as two distinct diseases and should be thoroughly distinguished to avoid futile treatment. Several researchers tried to find additional MRI indexes differentiating one from the other, such as Magnetic Resonance Parkinsonism Index, Magnetic Resonance Hydrocephalic Index, interpeduncular angle, midbrain area, and cortical thickness (Bianco et al., 2022; Ohara et al., 2020 ; Quattrone et al., 2020 ; Ugga et al., 2020 ; Virhammar et al., 2022). In our opinion, a portion of the two entities does overlap and share similar features, implying the transitory role of NPH mimics in the clinical course of PSP.…”
Section: Discussionmentioning
confidence: 99%
“…MRPI 2.0 has been found to be more feasible for evaluating PSP progression [ 17 ]. A more recent study showed certain limits to the usefulness of MRPI and MRPI 2.0 since significant overlaps were found with normal pressure hydrocephalus and PSP [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 To avoid the misdiagnosis of NPH and other neurodegenerative disorders, especially in patients with PSP who exhibit the clinical triad of NPH symptoms, radiological biomarkers with MRI are suggested. 11 , 12 Distinguishing NPH from neurodegenerative disorders is necessary to avoid shunt‐related complications such as infection and headache because shunt surgery is not likely to have beneficial effects in patients with neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of NPH studies indicated that the benefits of shunt implantation in patients with an initial diagnosis of idiopathic NPH persisted in only 32% of patients at 36 months, leading to a revised diagnosis in more than 25% of patients (AD, DLB, and PSP) 1 . To avoid the misdiagnosis of NPH and other neurodegenerative disorders, especially in patients with PSP who exhibit the clinical triad of NPH symptoms, radiological biomarkers with MRI are suggested 11,12 . Distinguishing NPH from neurodegenerative disorders is necessary to avoid shunt‐related complications such as infection and headache because shunt surgery is not likely to have beneficial effects in patients with neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%